The reliability and validity of gait analysis system using 3D markerless pose estimation algorithms - Liang, Shengyun; Zhang, Yu; Diao, Yanan; Li, Guanglin; Zhao, Guoru (Frontiers in Bioengineering and Biotechnology, 2022)
Quantifying kinematic gait for elderly people is a key factor for consideration in evaluating their overall health. However, gait analysis is often performed in the laboratory using optical sensors combined with reflective markers, which may delay the detection of health problems. This study aims to develop a 3D markerless pose estimation system, using OpenPose and 3DposeNet algorithms. Thirty participants performed a walking task. Sample entropy was adopted to study dynamic signal irregularity degree for gait parameters. Paired-sample t-test and intra-class correlation coefficients were employed to assess validity and reliability. Furthermore, the agreement between the data obtained by markerless- and marker-based measurements was assessed by Bland-Altman analysis. ICC [C, 1] indicating the test-retest reliability within systems were in almost complete agreement. There were no significant differences between the sample entropy of knee angle and joint angles of the sagittal plane by the comparisons of joint angles results extracted from different systems (p>0.05). ICC [A, 1] indicating the validity were substantial. This is supported by Bland-Altman plot of the joint angles at maximum flexion. Optical motion capture and single camera sensors were collected simultaneously, making it feasible to capture stride-to-stride variability. In addition, the sample entropy of angles were close to the ground_truth in the sagittal plane, indicating that our video analysis could be used as a quantitative assessment of gait, making outdoor applications feasible.